Hubungan Derajat Keasaman Saliva dan Karies Gigi pada Siswa Sekolah Menengah Atas - Mariati, Ni Wayan; Pangemanan, Damajanty H. C.; Bangun, Liasma K. (Universitas Sam Ratulangi, 2025)
Abstract: The prevalence of caries among people in the age group of 15-24 years is still high. North Sulawesi Province has a caries occurrence rate of 55%. The salivary pH value during resting period has the ability to predict caries status. This study aimed to determine the relationship between the degree of salivary acidity and dental caries in students of SMAN 1 Wori (senior high school). This was an analytical study with a cross-sectional design. Samples were obtained by using total sampling method. Salivary pH was examined using the spitting technique and dental caries was examined using the DMF-T index. The results obtained 114 students as respondents. Examination of the degree of acidity (pH) of saliva showed that the acid category occupied the highest frequency of 55 students (48.3%) and the least is the alkaline category of five students (4.4%). The highest number of DMF-T score was in the medium category, namely 35 respondents (30.7%), while the high and very high categories had the same number, namely 18 respondents (15.8%) each. The chi-square test obtained a p-value of 0.001 for the relationship between the degree of acidity (pH) of saliva and dental caries. In conclusion, there is a relationship between the degree of acidity (pH) of saliva and dental caries among students of SMAN 1 Wori. Keywords: saliva acidity; dental caries Abstrak: Prevalensi karies pada masyarakat dengan kelompok usia 15–24 tergolong tinggi. Provinsi Sulawesi Utara mempunyai angka terjadinya karies sebesar 55%. Nilai pH saliva selama periode istirahat memiliki kemampuan untuk memrediksi status karies. Penelitian ini bertujuan untuk mengetahui hubungan derajat keasaman saliva dan karies gigi di SMAN 1 Wori. Jenis penelitian ialah analitik dengan desain potong lintang Pengambilan sampel dengan menggunakan total sampling. Pada penelitian ini dilakukan pemeriksaan pH saliva dengan menggunakan teknik spitting dan pemeriksaan karies gigi dengan menggunakan indeks DMF-T. Hasil penelitian mendapatkan 114 siswa sebagai responden penelitian. Pemeriksaan derajat keasaman (pH) saliva memperlihatkan bahwa kategori asam menempati frekuensi paling tinggi (48,3%) dan yang paling sedikit ialah kategori basa (4,4%). Jumlah nilai DMF-T terbanyak pada kategori sedang (30,7%) sedangkan untuk kategori tinggi dan sangat tinggi mempunyai jumlah sama banyak (masing-masing15,8%). Hasil uji chi-square terhadap hubungan pH saliva dan karies gigi mendapatkan nilai p=0,001. Simpulan penelitian ini ialah terdapat hubungan antara derajat keasaman (pH) saliva dan karies gigi pada siswa di SMAN 1 Wori. Kata kunci: derajat keasaman saliva; karies gigi